Acceptance and Use of PeduliLindungi Application in Patients Based on Digital Health Literacy Competence - Nur Aisya, Nabila; Rachmani, Enny; Chuvita, Laila (Health Science UDINUS, 2023)
PeduliLindungi is a COVID-19 tracking application with a QR Code feature officially used for contact tracing in Indonesia. District General Hospital (RSUD) Tugurejo Semarang already has a QR Code Scan to enter the building. However, many patients have not used to utilize the scanner. Therefore, the researcher aimed to determine the acceptance and use of the PeduliLindungi app based on patients' digital literacy competence at RSUD Tugurejo, Semarang City. The research was descriptive and distributed questionnaires to 100 outpatients. The results showed that 41% of outpatients could use social media to communicate, and 31% used the internet to find health information. 54% of patients strongly agree that PeduliLindungi helped control Covid-19. The app's acceptance and use were mainly in patients aged 18–27. Patients with education who did not graduate from high school had the lowest average usage, 51.29. The difference in digital literacy competency scores between female and male patients was relatively high, namely 136.6 in women and 124.46 in men. The average digital literacy competence in the expert category was 61.05. Education regarding the PeduliLindungi app is necessary, especially for patients in the non-productive age group.